Photobleaching dynamics in small molecule vs. polymer organic photovoltaic blends with 1, 7-bis-trifluoromethylfullerene. Issue 11 (28th February 2018) - Garner, Logan E.; Nellissery Viswanathan, Vinila; Arias, Dylan H.; Brook, Colin P.; Christensen, Steven T.; Ferguson, Andrew J.; Kopidakis, Nikos; Larson, Bryon W.; Owczarczyk, Zbyslaw R.; Pfeilsticker, Jason R.; Ramamurthy, Praveen C.; Strauss, Steven H.; et al.
Abstract : C60 (CF3 )2 stabilizes OPV donors toward photodegradation. Abstract : Two organic photovoltaic (OPV) donor materials (one polymer and one small molecule) are synthesized from the same constituent building blocks, namely thiophene units, cyclopentathiophene dione (CTD), and cyclopentadithiophene (CPDT). Photobleaching dynamics of these donor materials are then studied under white light illumination in air with blends of PC70 BM and the bis-trifluoromethylfullerene 1, 7-C60 (CF3 )2 . For both the polymer and small molecule blends, C60 (CF3 )2 stabilizes the initial rate of photobleaching by a factor of 15 relative to PC70 BM. However, once the small molecule:C60 (CF3 )2 blend bleaches to ∼80% of its initial optical density, the rate of photobleaching dramatically accelerates, which is not observed in the analogous polymer blend. We probe that phenomenon using time-resolved photoluminescence (TRPL) to measure PL quenching efficiencies at defined intervals during the photobleaching experiments. The data indicates the small molecule donor and C60 (CF3 )2 acceptor significantly de-mix with time, after which the blend begins to bleach at approximately the same rate as the neat donor sample. The work suggests that perfluoroalkylfullerenes have great potential to stabilize certain OPV active layers toward photodegradation, provided their morphology is stable.